KEDUDUKAN ANAK AKIBAT PEMBATALAN PERKAWINAN SEDARAH DITINJAU DARI UNDANG-UNDANG NO 1 TAHUN 1974 TENTANG PERKAWINAN - Jinner Sidauruk (LPPM Universitas HKBP Nommensen, 2020)
Article 1 of the Marriage Law, Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on Almighty God. In the definition of marriage, we also see an element of bonding between a man and a woman as husband and wife. For this reason, husband and wife need to help and complement each other so that each can develop his personality to help and achieve spiritual and material well-being. In inbreeding has been carried out for a long time by people in certain areas who still have blood relations. Where this is done over and over again becomes a habit and then the marriage becomes a culture for a certain area. From the foregoing, it can be seen that inbreeding exists in Indigenous communities where Customary Law applies and Islamic societies that apply Islamic law. After the enactment of the Marriage Law No.1 of 1974 concerning marriage, marriages made with relatives or inbreeding have been restricted and even prohibited in the Marriage Law but if this is violated and occurs, the marriage can be canceled.